2019
DOI: 10.1101/532234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LSD impairs working memory, executive functions, and cognitive flexibility, but not risk-based decision making

Abstract: Psychiatric and neurodegenerative illnesses are characterized by cognitive impairments, in particular deficits in working memory, decision making, and executive functions including cognitive flexibility. However, the neuropharmacology of these cognitive functions is poorly understood. The serotonin (5-HT) 2A receptor might be a promising candidate for the modulation of cognitive processes. However, pharmacological studies investigating the role of this receptor system in humans are rare. Recent evidence demons… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Similarly, psilocybin decreased attentional tracking ability in HCs, which the authors speculated was due to the inability to inhibit distracting stimuli (303). More recently, retreatment with ketanserin (40 mg) normalized all LSD-induced cognitive deficits (302). Psychedelic induced impairment of aspects of cognitive flexibility was also observed in a probabilistic reversal learning paradigm in 19 HCs who received IV LSD (75µg) or placebo at two sessions, two weeks apart (Kanen 2021).…”
Section: Cognitive Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, psilocybin decreased attentional tracking ability in HCs, which the authors speculated was due to the inability to inhibit distracting stimuli (303). More recently, retreatment with ketanserin (40 mg) normalized all LSD-induced cognitive deficits (302). Psychedelic induced impairment of aspects of cognitive flexibility was also observed in a probabilistic reversal learning paradigm in 19 HCs who received IV LSD (75µg) or placebo at two sessions, two weeks apart (Kanen 2021).…”
Section: Cognitive Controlmentioning
confidence: 99%
“…Psychedelics transiently impair certain aspects of cognition in a dose-dependent manner (142,(300)(301)(302). For example, a study in HCs showed that LSD (100 µg) compared to placebo acutely impaired executive functions, cognitive flexibility, and working memory on the Intra/Extra-Dimensional shift task, and Spatial Working Memory task, but did not influence the quality of decision-making and risk taking on the Cambridge Gambling Task (302). Similarly, psilocybin decreased attentional tracking ability in HCs, which the authors speculated was due to the inability to inhibit distracting stimuli (303).…”
Section: Cognitive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The median estimated dosage reported in this survey of recreational use was 4g of dried mushroom, which is roughly equivalent to the 25mg (high) dose of psilocybin that is used as a therapeutic dose in laboratory settings 4,5,13 Investigations of the psychological and neural mechanisms underlying therapeutic effects of hallucinogens are still in a nascent stage. While most studies of the acute effects of hallucinogens demonstrate impairments in a number of perceptual and cognitive domains [26][27][28][29][30] , one recent study suggested a potential minute, acute attentional bene t of microdoses of LSD 31 . Another recent study demonstrated an improvement in cognitive exibility in patients with MDD after treatment with psilocybin 32 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is essential to acknowledge the limitations of relying exclusively on standardized methods. Cognitive batteries in psychedelics studies, such as those by Pokorny et al (2020), o en indicate cognitive impairments, but these results may not be very informative on their own. Instead, a more in-depth examination of speci c tasks related to attention, memory, and other cognitive processes is necessary, as well as studies that directly compare di erent drugs, like dextromethorphan and psilocybin.…”
mentioning
confidence: 99%